Perancangan Video Tutorial “Mechanic Shift Salesforce” United Tractors Bagi Mekanik Dan User - Aria Befrima Daffa; Heldi Heldi (Jurnal Mahasiswa Kreatif, 2023)
Optimization of video tutorial information media in the world of work is needed for mechanics and users at United Tractors, because it can have an impact and contribution to United Tractors, but because their performance is not optimal, a solution is needed to solve this problem. The purpose of this design is to create information media for the "Mechanic Shift Salesforce" feature that is informative, communicative, and effective for the performance of mechanics and users, easily understood as an SOP guideline for United Tractors. The designer makes information media about a new feature specifically for mechanics and users in maximizing their performance. Based on these issues, it is necessary to design a Video Tutorial in solving the problems faced by United Tractors. This design method is 4D which consists of: Define, Design, Develop, Desseminate. Define to find design solutions for mechanics and users at UT. Design is carried out in several steps including: pre-production, production, and post-production. Develop to test the video tutorial to one of the mechanics and users at UT. Desseminate or dissemination is supported by several supporting media that will be connected to video tutorials. Data analysis is carried out in 5W + 1H. What, what is the background of the design. Who, who is the target target in the design. Why, why this design is needed. When, when the issue occurred. Where, where the issue occurs. The main media of the design is a video tutorial building on the procedures and steps of using the "Mechanic Shift Salesforce" feature. Supporting media such as Guidebook, E-Guidebook, Poster, and X-Banner.